Development of measurement instruments for 21st century skills of elementary school students based on the STEAM approach: A study of validity and reliability - Zainil, Melva; Kenedi, Ary Kiswanto; Anita, Yesi; Mardin, Asna; Yulistina, Nova (International Journal of Innovative Research and Scientific Studies, 2025)
This study was conducted to develop a valid and reliable instrument to measure the 21st-century skills of elementary school students in the context of STEAM-based learning. The 21st-century skills include five main dimensions: critical thinking, creativity, collaboration, communication, and digital literacy. The research used a Research and Development (R&D) approach with stages including construct development, expert content validation, field testing, construct validity analysis using Confirmatory Factor Analysis (CFA), and reliability testing. The pilot sample consisted of 120 fifth-grade students from six elementary schools in West Sumatra Province. Content validation results showed a Content Validity Index (CVI) value of 0.89, while CFA analysis showed a good measurement model with a CFI value of 0.94 and an RMSEA value of 0.063. All dimensions showed high internal reliability, with Cronbach's Alpha values between 0.76 and 0.83 and Composite Reliability (CR) between 0.81 and 0.87. These results indicate that the developed instrument is suitable for use as a valid and consistent measure of elementary school students' 21st-century skills and can support contextual learning assessments relevant to future education demands.